Como se o mundo girasse em torno de uma balança: as representações sociais de bulimia e anorexia no ambiente virtual dos blogs - Letícia Tatiane Rezende Faleiro (2018)
The body, presented as a way of existing, receives strong cultural and social influences that fit it at the social dynamics of its time. Nowadays, the abomination of obesity as justification of the idea of health and the obedience to the norms to achieve success and happiness reflect the Western requirement of bodies adequacy to an ideal model related to thinness. Consumption and image are privileged by modern society, resulting in a growing movement around the "having" instead of "being. In interpersonal relationships, the contemporary society has been leading, through internet, new forms of interaction. It is in this characterization of the contemporary society that rooted the growth of eating disorders and the virtual sharing of interests, values and aspirations that allows the feeling of belonging among those who have such disorders, revealing the complex identity dynamics of intergroup relations. The possibility of subjects to interact virtually anonymously and freely favors social representations and practices of on anorexia and bulimia that could suffer social coercion in other spaces, breaking the need to keep the symptoms secret and increasing the possibilities of searching information and support. Beyond an individual clinical phenomenon, pro-anorexia and pro-bulimia blogs present themselves as a broad-based communication vehicle, demonstrating aspects of psychosocial sphere related to eating disorders that are in a group context that sustains them. Thinking about the striking impact of forms of relationship with the body that stand out in contemporary experience, our study aimed to understand anorexia and bulimia from the universe of social representations as products and processes of appropriation and psychosocial elaboration of reality. The general objective of the research was to identify and analyze social representations and practices on anorexia and bulimia, from testimonials published in proanorexia and pro-bulimia public access blogs by people affected by those eating disorders. A documentary research through the available testimonies was conducted on three public access blogs created for sharing of experiences about anorexia and bulimia. The textual data were submitted to the lexicographic analysis with the aid of IRAMUTEQ software. The lexical analysis allowed us to distinguish in the dendrogram five textual classes that are related to each other and are composed by a set of at least twenty-five words that have greater affinity with the class that they are part of. We have identified that the social representations of anorexia and bulimia shared in blogs permeate family relationships, the ambivalence of feelings, the identity space established in the virtual environment, the bonds of friendship and the adoption of practices in search of the skinny body. For this understanding, it is necessary to consider the social construction of the body image and the feeling of inadequacy before shared ideal body conceptions as well as the incomprehension in the social relations of the meanings shared by people with anorexia and bulimia who sometimes distance themselves from medical knowledge. Anorexia and bulimia emerged as mediators and predictors of experience of these subjects, so that the social representation of anorexia and bulimia presented a centrality in the experience, even though in a dramatic and ambivalent way, predicting and justifying behaviors